Development of Participation Model in Family and Community for Increase Rate of Antenatal Care Before 12 Weeks in Ngaeng Health Promoting Hospital, Pua District, Nan Province - วงศ์ถิรกุล ฐิตาภร (Journal of Health Science of Thailand, 2021)
The purposes of this research and development were to develop and assess the participation model of family and community to increase the rate of antenatal care before 12 weeks in Ngaeng health promoting hospital, Pua District, Nan Province. The sample recruited by purposive sampling included of new pregnant cases who attended antenatal care during 1 October 2015 - 30 June 2018, altogether 42 persons. The tools of this research were the developed participation model, SWOT analysis, focus group interviews and participant observation, brochures, public relations, community amplifier, Line group and questionnaires. Data were analyzed by descriptive statistics, frequency, mean, standard deviation and content analysis The results of the model were as follow: (1) promotion of family participation, (2) integration of community and network partners, (3) participation of public health facilities in the area, and (4) knowledge enhancement. The results of this study found that family and community actively participated to supported reaching a good level; the pregnant women had high level of knowledge on prenatal care (85.71 percent of the cases) and 14.29% of them at moderate level. The rate of antenatal care before 12 weeks increased from 71.43, 88.89 to 90.00 percent during 2016 to 2018, respectively